The Influence of Perception of The Quality of The Charter Bus Fleet And Perception of Travel Service Quality Towards Customer Decision To Use PO Nabaru Jasa Trans Tourism Bus Service in Semarang City - Bagus Yunianto Wibowo (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
AbstractThe purpose of this research is to analyze the influence of perception of tourism bus fleet quality (X1) and perception of the quality of travel services (X2) on customer decision (Y) using Nabaru Jasa Trans tourism bus company in Semarang City. The methods of data collecting was conducted by observation and questionnaire. The questionnaire used semantic differential numeric scale with 10 rating score. The sampling technique used was saturated sampling or census with a total of 100 respondents. The analysis methods used were validity test, reliability test, descriptive analysis, normality test, multicollinearity test, heterokedasticity test, linearity test, multiple linear regression analysis, t test, F test, and coefficient of determination. The result of this research shows that perceived bus service quality and perceived travel quality simultaneosly influences significantly on customer decision to use Nabaru Jasa Trans tourism bus company in Semarang City.  Keyword: Tourism Buses, Travel Services, Customer Decision